A Water Molecule Triggers Guest Exchange at a Mono‐Zinc Centre Confined in a Biomimetic Calixarene Pocket: a Model for Understanding Ligand Stability in Zn Proteins. Issue 55 (11th August 2021) - Brunetti, Emilio; Marcelis, Lionel; Zhurkin, Fedor E.; Luhmer, Michel; Jabin, Ivan; Reinaud, Olivia; Bartik, Kristin
Abstract: In this study, the ligand exchange mechanism at a biomimetic Zn II centre, embedded in a pocket mimicking the possible constrains induced by a proteic structure, is explored. The residence time of different guest ligands (dimethylformamide, acetonitrile and ethanol) inside the cavity of a calix[6]arene‐based tris(imidazole) tetrahedral zinc complex was probed using 1D EXchange SpectroscopY NMR experiments. A strong dependence of residence time on water content was observed with no exchange occurring under anhydrous conditions, even in the presence of a large excess of guest ligand. These results advocate for an associative exchange mechanism involving the transient exo‐coordination of a water molecule, giving rise to 5‐coordinate Zn II intermediates, and inversion of the pyramid at the Zn II centre. Theoretical modelling by DFT confirmed that the associative mechanism is at stake. These results are particularly relevant in the context of the understanding of kinetic stability/lability in Zn proteins and highlight the key role that a single water molecule can play in catalysing ligand exchange and controlling the lability of Zn II in proteins. Abstract : The ligand exchange mechanism at a Zn II centre embedded in a calix[6]arene pocket mimicking the constrains induced by a proteic structure was probed by 1D EXSY NMR experiments and DFT calculations. Results highlight: i) the very high kinetic stability of a tetrahedral Zn II centre when coordination of a fifth ligand is precluded by the environment, ii) the necessary associative double‐exchange mechanism for ligand exchange, and iii) the key role that a single water molecule can play in catalysing the exchange.